Faktor-Faktor Yang Berhubungan Dengan Kelainan Kongenital Pada Anak di RSPAD Gatot Soebroto - Sri Ellyati; Kusharisupeni Kusharisupeni; Luknis Sabri (JOURNAL EDUCATIONAL OF NURSING(JEN), 2019)
There are several methods for detecting congenital abnormalities, the most popular method at present is 3-dimensional ultrasound, MRI. The purpose of this study was to determine the factors associated with congenital abnormalities in children at Gatot Soebroto Central Jakarta Hospital in 2013. The design of this study was quantitative with a cross sectional approach. Population in the study were all children who had been treated in the Gatot Soebroto Children's Hospital recorded in the medical record for the period of January- December 2013 there were 707 children with 264 children with congenital abnormalities and 443 children without congenital abnormalities, the number of samples taken was 100 children using systematic random sampling. Data were analyzed by univariate, bivariate and multivariate analysis. The results were obtained as many as 57 (57%) who did not experience congenital abnormalities and 43 (43%) had congenital abnormalities. There is a relationship between education and congenital disorders. After multivariate analysis, the dominant variable is the labor variable associated with congenital abnormalities in children with p =0.039 and OR = 3.705 (95% CI: 1.067-12.870), while the variables of education, maternal age, gestational age, occupation, parity, income, LBW is a confounding variable. More complete information about the importance of knowing congenital abnormalities in children can be detected early and can be avoided if the mother consumes nutritious food, does not smoke, does not take medicine without the knowledge of the doctor, vaccination. Keywords: Congenital Disorders, Children